Analisis Tarif Pajak (PPH 21) dan Sosialisasi Perpajakan Terhadap Kepatuhan WPOP Karyawan - Hanggara, Dipta Wira; Tannar, Oryza (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The majority of employees in Indonesia are subject to an automatic tax withholding system through the Article 21 Income Tax (PPh 21) mechanism. However, compliance in submitting the Annual Tax Return (SPT) remains relatively low. This study aims to analyze the effect of Article 21 Income Tax (PPh 21) rates and tax socialization on the compliance of individual taxpayers (WPOP) among employees of PT Puspa Agro Sidoarjo. This research uses a quantitative approach with data collected through online questionnaires and analyzed using the Structural Equation Modeling method with the Partial Least Squares (PLS-SEM) approach through SmartPLS 4.0 software. The results indicate that PPh 21 tax rates have a positive and significant effect on tax compliance (coefficient = 0.727; t = 11.025; p = 0.000), and tax socialization also has a positive and significant effect (coefficient = 0.274; t = 4.166; p = 0.000). Both variables explain 64% of the variation in taxpayer compliance, with the dominant influence coming from tax rates (f² = 0.453). These findings emphasize that managing fair tax rates and improving the quality of tax information dissemination are essential to increase taxpayer compliance.